Creative teaching incorporated into the design of a functional costume for pet dogs: A case study of Shiba Inu - YI-CHING TSENG; TSAI-FENG CHENG; RU-CHU SHIH; SHU-FEN TSENG; SHI-JER LOU (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: The study’s overarching goal is to find ways to incorporate the functional clothing of pet dogs into creative teaching to use imaginative thought to stimulate students’ creativity and hone their abilities by having them put them to practical use while also taking into account the practical concerns of safety, comfort, and special applications.Method: An expert validity-evaluation questionnaire of pet clothing and a pet dog functional clothing rating scale, both ranked on a Richter Likert five-point scale, were compiled after a discussion and analysis of the relevant literature, and the questions were tailored to the study’s aim. Part 1 of the questionnaire is dedicated to the expert and owner’s personal details, Part 2 to the dog itself, and Part 3 to the expert’s and owner’s thoughts on the best apparel for their pet.Findings: The survey data shows that when shopping for dog clothing, respondents care most about three factors: functionality and comfort (12.5%), safety and quality (14.3%), and practicality (16.1%). Most dog owners (45.5% of those surveyed) say they are willing to spend between NT$500 and NT$1,000 on a costume for their pet, and those same people (45.5% of those surveyed) say they currently own five to nine different pet dog costumes.Implications/Novel Contribution: According to the research results, there has been a rise in the demand for high-quality pet products like food, clothing, and housing. Industrial connections made possible through costume design curriculum materials will increase the field’s applicability, pique students’ interest, and bridge the gap between the business world and universities.